Principal Direction Of Economic Development: Digitalization Process - Dilnavoz Abdiyeva (International Journal of Advanced Science and Technology, 2020)
On the basis of international marketing principles, the sewing and knitwear market is segmented using cluster method. It is important that the Republic of Uzbekistan conducts a policy of efficient use of the benefits of globalization in exports in the course of economic reforms. This, in turn, requires that the export-oriented policy of the producers is carried out on a large scale, without improving the system of its promotion, the intended goal can not be achieved.